PERMASALAHAN ANGKATAN KERJA DI INDONESIA : KENDALA GENDER DAN PEMBATASAN PEKERJAAN BAGI WANITA PERSPEKTIF PATRIARKI DAN FENIMISME - Aulya Arzuliany; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
Gender is a social concept that has a significant influence on the attitudes, traits and standards set by society towards women and girls. In Indonesia, there are certain jobs that are considered unsuitable or inappropriate for women, which hinders the achievement of gender equality in the workplace. This article aims to discuss the gender pay gap that exists in the workplace in Indonesia, with a focus on the wage gap between men and women. In this context, the article also discusses these issues in relation to patriarchy and feminism.Through literature analysis, the article investigates related issues, such as the existence of too much or too little work for women, which results in difficulties for women in gaining fair access in the workplace. The purpose of this study is to critically examine the impact of patriarchy on the level of stress experienced by women in the workplace, and analyze feminist strategies that can be used to address these issues.The findings of this study emphasize the importance of gender equality awareness in the workplace, as well as the need for concrete actions to address the low esteem of women in Indonesia in the context of employment.